Mixed Forestation Outperforms Pure Stands in Soil Carbon Sequestration and Stability - Xiangyang Shu; Dechao Chen; Ji Chen; Zhenghu Zhou; Yiqi Luo; Yanyan Zhang; Hao Tang; Dongzhou Deng; Longlong Xia (Global Change Biology, 2026)
Forestation is a pivotal nature‐based strategy for enhancing soil organic carbon (SOC) sequestration, yet the differential impacts of pure versus mixed‐species plantations on SOC fractions and stability remain poorly quantified at a global scale. To address this knowledge gap, we performed a meta‐analysis of 4052 observations from 102 sites and showed that mixed forestation significantly increases SOC, particulate organic carbon (POC), and mineral‐associated organic carbon (MAOC) by 64.3%, 86.9%, and 65.3%, respectively, whereas pure forestation enhances SOC and POC but has no significant impact on MAOC. Critically, pure forestation reduced the MAOC:POC ratio—a key indicator of SOC stability—by 24.9%, while mixed forestation maintained or enhanced it. Prior land use type was the dominant regulator of SOC fraction responses, with plantation age further moderating SOC accrual and stability. Mixed forestation also promoted greater soil nitrogen, microbial biomass, and dissolved organic carbon, supporting MAOC formation and SOC stability. Our results demonstrate that mixed forestation simultaneously enhances SOC storage and stability, offering a more resilient pathway for terrestrial carbon sequestration under global change. These findings underscore the need to prioritize mixed‐species plantations in reforestation policies to achieve climate mitigation and ecosystem restoration goals.